The Qur’an and the Sunnah on Violence, Armed Struggle, and the Political Process - 'AbdulHamid A. AbuSulayman (International Institute of Islamic Thought, 1991)
Translation In the name of Allah, Most Gmcious, Most Merciful. 1. To those against whom War is made, permission is given (to fight), because They are wronged-and verily, Allah is Most Powerful For their aid- (They are) those who have Been expelled from their homes In defiance of right- (For no cause) except That they say, “Our Lord Is Allah.“ Did not Allah Check one set of people By means of another There would surely have been Pulled down monasteries, churches, Synagogues, and mosques, in which The name of Allah is commemorated In abundant measure. Allah will Certainly aid those who Aid His (cause)-for verily Allah is Full of Strength, Exalted in Might, (Able to enforce His Will). Al Hajj {22:39-40) 2. Fight in the cause of Allah Those who fight you, But do not transgress limits; For Allah loveth not transgressors. And slay them Wherever ye catch them, And turn them out From where they have Turned you out; ...